Historical and comparative analysis of exaggeration in Arabic and Persian rhetoric - Aliakbar Kamalinahad; Sohrab Ahmadi (مطالعات زبانی و بلاغی)
One of the Figures of Speech is exaggeration that in the most rhetorical Arabic and Persian books, extremes in describing someone or something is defined.provides clarity use first Persian Rhetoric scholars of rhetorical Arabic at Bring up theoretical issues, course of comparative and historical context the Figures of Speech in the Arabic and Persian rhetoric.Do This Research the historical evolution of exaggeration in the Arabic and Persian rhetoricfrom the creation of this arrayuntil the completion ofits division and Present clear Vision from Genesis of theoretical and dividing it into three rank Bombast, exaggeration and hyperbole, Definitions, names and different classifications of this array.It also shows what developments and progress has passed During Its history. How and from whom Persian and Arabic rhetoric scholars are affected in definition and analysis and divided to what groups? On what principles is it based the point of view of rhetoric esthetics of array? What is the importance and position of this array in their eyes?